2017
DOI: 10.1111/jvh.12690
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and structural changes related to hepatitis E virus antigen and its expression in testis inducing apoptosis in Mongolian gerbil model

Abstract: Hepatitis E virus (HEV) infection has been associated with a wide range of extrahepatic manifestations, so this study was designed to examine the effect and role of HEV on structural and molecular changes in the testicular tissues of Mongolian gerbils experimentally infected with swine HEV. HEV RNA was first detected in testis at 14 days post-inoculation and reached a peak between 28 and 42 days later with viral load between 3.12 and 6.23 logs/g by PCR assays. Changes including vacuolation, sloughing of germ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…The pathogenesis of HEV in the genital system is not largely understood. HEV-4 could disrupt the blood-testis barrier in the Mongolian gerbils' model and BALB/c mice, inducing the necrosis of tubules, germ cell apoptosis, and testicular damage [22,32]. In addition, HEV RNA was detected in pig semen in Shaanxi Province, China, and the semen of infertile males [23,33].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of HEV in the genital system is not largely understood. HEV-4 could disrupt the blood-testis barrier in the Mongolian gerbils' model and BALB/c mice, inducing the necrosis of tubules, germ cell apoptosis, and testicular damage [22,32]. In addition, HEV RNA was detected in pig semen in Shaanxi Province, China, and the semen of infertile males [23,33].…”
Section: Discussionmentioning
confidence: 99%
“…They reported that HEV itself does not damage the tissues or site; it is the immune system that results in these histopathological alternations in the infected tissues [41]. In chronic cholestatic liver dysfunction model induced by bile duct ligation in mice and chickens, testes showed many structural changes including tubular distortion and atrophy, associated with thick irregular boundaries, vacuolation, disorganized epithelium, and exfoliated cells [42,43]. These changes were reported to result from "the detergent-like effect of the toxic bile acids" which is known to enhance membranous lipid polarity and fluidity [44,45].…”
Section: Other Types Of Liver Fibrosismentioning
confidence: 99%
“…These models only allowed budding as a mechanism for viral particle production from syncytia, assuming that no apoptosis occurs from fused cells [ 158 ]. Recent reports suggest that this may not be the case [ 159 , 160 , 161 , 162 , 163 , 164 , 165 ], depending on the virus; adjustments during model development and fitting can resolve such issues. In their model, Jacobsen and Pilyugin found that an increase in burst size would allow for tumor control.…”
Section: Modeling Specific Mechanisms Of Actionmentioning
confidence: 99%